Dominant Plant Functional Group Determine the Response of the Temporal Stability of Plant Community Biomass to 9-Year Warming on the Qinghai–Tibetan Plateau - Li, Chengyang; Lai, Chimin; Peng, Fei; Xue, Xian; You, Quangang; Liu, Feiyao; Guo, Pinglin; Liao, Jie; Wang, Tao (Frontiers in Plant Science, 2021)
Ecosystem stability characterizes ecosystem responses to natural and anthropogenic disturbance and affects the feedback between ecosystem and climate. A 9-year warming experiment (2010-2018) was conducted to examine how climatic warming and its interaction with the soil water stand impact plant community aboveground biomass (AGB) stability of an alpine meadow located in the central of the Qinghai-Tibetan Plateau (QTP). Under a warming environment, the AGB percentage of grasses and forbs significantly increased but that of sedges decreased regardless of the soil water stands. The warming effects on plant AGB varied with annual precipitation. Under dry stand, the AGB showed no significant change under warming in the normal and relatively wet years, but it significantly decreased in relatively drought years (13% in 2013 and 10% in 2015). Under wet stand, the AGB showed no significant change under warming in the normal and relatively drought years, while it significantly increased in relatively wet years (11% in 2017 and 14% in 2018). Warming significantly decreased the plant community and sedges AGB stability. Species richness keeps unchanged in a warming climate both under dry and wet stands. The temporal stability of AGB of sedges (dominant plant functional group) explained 52.95% of the temporal stability of plant community AGB variance. Our results indicate that plant biomass is more sensitive to the annual precipitation variation in a warming climate. Our findings highlight that the plant community AGB stability was regulated by the dominant plant functional group of alpine meadow in which species diversity is relatively low.